Modern Corporate Management Technologies Are the Basis of Organizational Economy Development - Vohobov Hikmatillo Mamirjon oglu (Zien Journals, 2022)
This article provides information on modern corporate governance, its important aspects and ways to achieve economic efficiency through management incentives.
Keywords: corporate governance; technology; efficiency; investment